Evaluation of Vaccine Safety After the First Public Sector Introduction of Typhoid Conjugate Vaccine—Navi Mumbai, India, 2018. (27th January 2021) - Longley, Ashley T; Date, Kashmira; Luby, Stephen P; Bhatnagar, Pankaj; Bentsi-Enchill, Adwoa D; Goyal, Vineet; Shimpi, Rahul; Katkar, Arun; Yewale, Vijay; Jayaprasad, Niniya; Horng, Lily; Kunwar, Abhishek; et al.
Abstract: Background: In December 2017, the World Health Organization (WHO) prequalified the first typhoid conjugate vaccine (TCV; Typbar-TCV). While no safety concerns were identified in pre- and postlicensure studies, WHO's Global Advisory Committee on Vaccine Safety recommended robust safety evaluation with large-scale TCV introductions. During July–August 2018, the Navi Mumbai Municipal Corporation (NMMC) launched the world's first public sector TCV introduction. Per administrative reports, 113 420 children 9 months–14 years old received TCV. Methods: We evaluated adverse events following immunization (AEFIs) using passive and active surveillance via (1) reports from the passive NMMC AEFI surveillance system, (2) telephone interviews with 5% of caregivers of vaccine recipients 48 hours and 7 days postvaccination, and (3) chart abstraction for adverse events of special interest (AESIs) among patients admitted to 5 hospitals using the Brighton Collaboration criteria followed by ascertainment of vaccination status. Results: We identified 222/113 420 (0.2%) vaccine recipients with AEFIs through the NMMC AEFI surveillance system: 211 (0.19%) experienced minor AEFIs, 2 (0.002%) severe, and 9 serious (0.008%). At 48 hours postvaccination, 1852/5605 (33%) caregivers reported ≥1 AEFI, including injection site pain (n = 1452, 26%), swelling (n = 419, 7.5%), and fever (n = 416, 7.4%). Of the 4728 interviews completed at 7 days postvaccination, the most reported AEFIs included fever (n = 200, 4%), pain (n = 52, 1%), and headache (n = 42, 1%). Among 525 hospitalized children diagnosed with an AESI, 60 were vaccinated; no AESIs were causally associated with TCV. Conclusions: No unexpected safety signals were identified with TCV introduction. This provides further reassurance for the large-scale use of Typbar-TCV among children 9 months–14 years old. Abstract : Using data from passive surveillance, telephone interviews, and active surveillance for adverse events of special interest, no safety signals were identified from the first public sector introduction of Typbar-TCV among children 9 months–14 years old in Navi Mumbai, India.